2011
DOI: 10.5465/amj.2009.0211
|View full text |Cite
|
Sign up to set email alerts
|

Darwinians, Communitarians, and Missionaries: The Role of Founder Identity in Entrepreneurship

Abstract: Drawing on social identity theory, we explore the identities, behaviors, and actions of 49 firm founders in the sports-related equipment industry. Our analysis suggests the existence of three pure types of founder identities and shows how these identities systematically shape key decisions in the creation of new firms, thereby "imprinting" the start-ups with the founders' distinct self-concepts. We synthesize our findings in a typology that sheds light on the heterogeneous meanings that founders associate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
832
2
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 688 publications
(888 citation statements)
references
References 48 publications
38
832
2
16
Order By: Relevance
“…Social identity, in turn, affects intra-and interpersonal experiences as people perceive and evaluate themselves and others according to these social group memberships. Indeed, management scholars have studied numerous workplace phenomena from the perspective of social identity theory such as foundersÕ beliefs and entrepreneurial outcomes (Fauchart & Gruber, 2011), family responsibilities and career outcomes (Lobel & St. Clair, 1992) and organizational attractiveness (Turban & Greening, 1997). Perhaps the largest body of organizational research stemming from this perspective relates to demographic factors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Social identity, in turn, affects intra-and interpersonal experiences as people perceive and evaluate themselves and others according to these social group memberships. Indeed, management scholars have studied numerous workplace phenomena from the perspective of social identity theory such as foundersÕ beliefs and entrepreneurial outcomes (Fauchart & Gruber, 2011), family responsibilities and career outcomes (Lobel & St. Clair, 1992) and organizational attractiveness (Turban & Greening, 1997). Perhaps the largest body of organizational research stemming from this perspective relates to demographic factors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Within the mainstream entrepreneurship domain, research on entrepreneurial identity considers that entrepreneurial activities impart meaning, and that they are thus an expression of an individual's identity or self-concept (Cardon et al, 2009;Fauchart & Gruber, 2011;Cardon et al, 2013). Social aspects of an individual's self-concept are central to entrepreneurship research, since new venture creation is an inherently social activity (Fauchart & Gruber, 2011).…”
Section: Entrepreneurial Identitymentioning
confidence: 99%
“…Social aspects of an individual's self-concept are central to entrepreneurship research, since new venture creation is an inherently social activity (Fauchart & Gruber, 2011). New ventures are intimately intertwined with the entrepreneur's identity (Shepherd & Haynie, 2009) and entrepreneurial identity is central to entrepreneurial passion (Cardon et al, 2013).…”
Section: Entrepreneurial Identitymentioning
confidence: 99%
“…Self-identity is "the extent to which performing [a] behavior is an important part of one's self concept" (Terry et al 1999: 226), and is shaped by both personal and social factors (Brewer 1991, Stryker and. A recent stream of research has demonstrated the importance of self-identity in decisions associated with both entrepreneurship and commercialization (Fauchart and Gruber 2011, Jain et al 2009, Powell and Baker 2014 and innovation communities (Bagozzi and Dholakia 2006).…”
Section: Self-identitymentioning
confidence: 99%
“…I use the launch of the Apple App Store and its effect on underground innovation communities (Mollick 2005) as a quasi-experiment to examine this issue. Drawing on the existing literature, I suggest that this decreased commercialization activity may be the result of one of two potential mechanisms: a general dis-utility of profit seeking among community members or else the self-identity of community members (Fauchart and Gruber 2011, Hogg et al 1995, Tajfel and Turner 1986. In a second study, I explore these potential mechanisms using data from an original longitudinal survey of open source developers.…”
Section: Introductionmentioning
confidence: 99%